2012
DOI: 10.1111/j.1440-1746.2011.06938.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus correlates with increased risk of pancreatic cancer: A population‐based cohort study in Taiwan

Abstract: Diabetes < 2 years' duration is associated with pancreatic cancer and could be an early manifestation of pancreatic cancer. Long-standing diabetes was not found to be a risk factor for pancreatic cancer in Taiwan's patients. Old age, chronic pancreatitis, gallstones and hepatitis C infection are other risk factors for pancreatic cancer. These high-risk patients should undergo close follow-up programs for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 18 publications
4
94
0
8
Order By: Relevance
“…2). A recent cohort study in Taiwan showed that in addition to age, CP (HRZ19.40), gallstones (HRZ2.56), and hepatitis C infection (HRZ3.08) were significant factors predicting PC; patients with concurrent DM and CP had a dramatically elevated risk of developing PC (HRZ33.52), compared with subjects without these comorbidities (Liao et al 2012). …”
Section: Diabetes (And Obesity) As a Cause Of Pcmentioning
confidence: 99%
“…2). A recent cohort study in Taiwan showed that in addition to age, CP (HRZ19.40), gallstones (HRZ2.56), and hepatitis C infection (HRZ3.08) were significant factors predicting PC; patients with concurrent DM and CP had a dramatically elevated risk of developing PC (HRZ33.52), compared with subjects without these comorbidities (Liao et al 2012). …”
Section: Diabetes (And Obesity) As a Cause Of Pcmentioning
confidence: 99%
“…Table 1A summarizes epidemiological studies that show pancreatic cancer risk and cancer mortality associated with metformin use while Table 1B presents observational studies and clinical trials on overall cancer risk and mortality in relation to metformin use. While some studies show a reduction in pancreatic cancer [35][36][37][38][39] and overall cancer risk [37,[39][40][41][42][43][44][45] among diabetic metformin users, there are also studies that report no significant difference in cancer risk among diabetics who take metformin compared to patients who take other anti-diabetic treatments [36,[46][47][48][49][50][51]. These conflicting results may be explained by differences in the study population, the confounding factors accounted for during statistical analysis and the selected study design (e.g., cohort versus case-control).…”
Section: Chemopreventive Properties Of Metforminmentioning
confidence: 60%
“…Whether the coexistence of CP with DM increases the overall risk of PC is unclear. In a population based cohort study by Liao et al [20], risk of PC in patients with CP and DM combined was higher than that for patients with CP alone (HR= 33.52 vs HR=19.4). This finding is confounded by the fact that diabetes could be a manifestation of PC in CP, rather than a risk factor.…”
Section: Pathogenesis Of Pancreatic Cancer In Chronic Pancreatitismentioning
confidence: 91%